Bodily Communication in Volleyball Between Human and Experimental Sciences - Raiola, Gaetano (Richtmann Publishing, 2012)
Bodily communication affects the relationship and exchanges between people and encourages cooperation throughoutsigns, symbols, facial expression, spaces and distances. It has psychology, social and cultural aspects and the fundamentalsare: context, sender, receiver, channel and code in a logical and analog form of manifestation. Volleyball is very fast sports gamebecause of the compulsory rule of rejected touch of the ball and the little dimension of the game court and in this case the bodilycommunication could be an important phenomenon. The scientific literature survey does not found any evidence about appliedstudy on both sports and bodily communication skills, thus could be useful to investigate by integrated vision. The purpose is toverify if any technical skills of the attack of volleyball may be influenced by bodily communication. The method is theoreticalargumentative,in one hand, and experimental, in the other one, by using performance analysis methodology and analyst team.This approach is innovative and complex and could be a partial solution to quantitative and qualitative question in evaluationprocess of any sports. The result categorizes the bodily communication in functional, diagnostic and tactics mode and thepercentage is over Â¼ of all outcomes and it has divided in three technical skills.Discussion is based by studies of the perceptionand action, human movement, motor control and learning, anticipation skills of motor imagery. Its development is desirable toenlarge the knowledge on these filed. Its development is desirable to enlarge the knowledge on the field of human sciences.